2017
DOI: 10.1007/s00284-017-1270-6
|View full text |Cite
|
Sign up to set email alerts
|

Bdm-Mediated Regulation of Flagellar Biogenesis in Escherichia coli and Salmonella enterica Serovar Typhimurium

Abstract: Synthesis of the flagellar apparatus in Escherichia coli is mediated via complex regulatory pathways. A previous study indicated that the protein encoded by the biofilm-dependent modulation (bdm) gene is linked closely with a regulatory pathway for flagellar assembly. However, the specific role of Bdm in flagellar biogenesis remains unknown. Herein, we showed that Bdm interacts with FlgM and inhibits its function as an anti-σ28 factor, which induces the transcription of flagellar late-class genes in E. coli. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Before the assembly of the hook-basal body structure, it is held inactive by the anti-σ 28 factor, flgM ( 59 ). YddX, a biofilm-dependent modulation protein (BDM) homolog, interacts with FlgM to repress its function as an anti-σ 28 factor ( 60 ). Our study observed a significant downregulation of yddX in the knockout strains.…”
Section: Discussionmentioning
confidence: 99%
“…Before the assembly of the hook-basal body structure, it is held inactive by the anti-σ 28 factor, flgM ( 59 ). YddX, a biofilm-dependent modulation protein (BDM) homolog, interacts with FlgM to repress its function as an anti-σ 28 factor ( 60 ). Our study observed a significant downregulation of yddX in the knockout strains.…”
Section: Discussionmentioning
confidence: 99%
“…Before the assembly of hook-basal body structure, it is held inactive by the anti-σ 28 factor, flgM [38]. YddX, a BDM homolog (Biofilm-dependent modulation protein) interacts with FlgM to repress its function as an anti-σ 28 factor[39]. Our study observed a significant downregulation of yddX in the knockout strains.…”
Section: Discussionmentioning
confidence: 81%